Civil liability of the arbitrator - Guettaf, Hafid (Journal of Human Sciences, 2021)
If the jurists have drawn the parameters of civil liability with both contractual and default types long ago, then the application of its provisions to the actions issued by the arbitrator on the occasion of the exercise of his mission carries prejudice to the dispute parties or to others which was unacceptable by all given the nature of the arbitration. While some considered the arbitrator a contracting person establishing his responsibility, others considered him a judge of immunity eliminating from him any responsibility; between these two opinions, the doctrine and jurisprudence have created, in light of the legislative vacuum, its own rules and principles. With regard to the different opinions, we tried, in this study, to adjust this issue in order to achieve the desired arbitration security.